THE USING OF SOCIAL NETWORKS AS A HEALTH RISK - Milošević, Zoran G (Acta medicae Medianae, 2021)
Social networks represent the most used type of communication. They are the largest virtual community and an inexhaustible source of information. The essential characteristic of social networks is virtual socializing and communication between people around the world. Today, it is known that excessive use of social networks for an extended period can cause significant health problems. The most common health problems are highlighted in this paper, and they are addiction, impaired concentration and attention, negative impact on intellectual abilities, increased levels of stress and fatigue, and negative impact on emotions. It is a fortunate circumstance that it is possible to reduce the negative impact of social networks on health. It is advised to limit the time of using social networks. It is best to connect to social networks from time to time and to look at the content that is offered to you several times during the day. It would be advisable to have access at a time that is convenient and limited for you.